Screening for 32 per- and polyfluoroalkyl substances (PFAS) including GenX in sludges from 43 WWTPs located in the Czech Republic - Evaluation of potential accumulation in vegetables after application of biosolids - Semerád, Jaroslav; Hatasová, Nicolette; Grasserová, Alena; Černá, Tereza; Filipová, Alena; Hanč, Aleš; Innemanová, Petra; Pivokonský, Martin; Cajthaml, Tomáš (Chemosphere, 2020)
Highly persistent, toxic and bioaccumulative per - and polyfluoroalkyl substances (PFAS) represents a serious problem for the environment and their concentrations and fate remain largely unknown. The present study consists of a PFAS screening in sludges originating from 43 wastewater treatment plants (WWTPs) in the Czech Republic. To analyze an extended group of PFAS consisting of 32 PFAS, including GenX and other new replacements of older and restricted PFAS in sludge, a new method was optimized and validated using pressurized solvent extraction, followed by the SPE clean-up step to eliminate the observed matrix effects and LC-MS/MS. The results revealed high PFAS contamination of sewage sludge, reaching values from 5.6 to 963.2 ng g-1. The results showed that in the majority of the samples (about 60%), PFOS was the most abundant among the targeted PFAS, reaching 932.9 ng g-1. Approximately 20% of the analyzed samples contained more short-chain PFAS, suggesting the replacement of long-chain PFAS (especially restricted PFOA and PFOS). GenX was detected in 9 samples, confirming the trend in the use of new PFAS. The results revealed that significantly higher contamination was detected in the samples from large WWTPs (population equivalent > 50,000; p-value <0.05). Concerning the application of sludge in agriculture, our prediction using the respective PFAS bioconcentration factors, the observed concentrations, and the legislatively permitted management of biosolids in Czech Republic agriculture revealed that PFAS can cause serious contamination of cereals and vegetables (oat, celery shoots and lettuce leaves), as well as general secondary contamination of the environment.
Keywords: průmyslová hnojiva; Waste Water; látky znečišťující půdu; odpadní voda; odpadní vody; kyseliny alkansulfonové; Česká republika; GenX; Wastewater treatment plant; Sewage; Alkanesulfonic Acids; Bioaccumulation; fluorokarbony; Czech Republic; kontaminace potravin; Sludge; PFOS; Soil Pollutants; Fluorocarbons; zelenina; Water Purification; Wastewater; Screening; Tandem Mass Spectrometry; Fertilizers; Propionates; chromatografie kapalinová; Food Contamination; propionáty; tandemová hmotnostní spektrometrie; Food contamination; Chromatography, Liquid; Biosolids; biosolidy; Vegetables; čištění vody; bioakumulace